1994
DOI: 10.1002/hc.520050207
|View full text |Cite
|
Sign up to set email alerts
|

The reaction of vicinal triketones with cumulative phosphorus ylides. Synthesis of phosphoranylidenecyclobutanes

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Compound 4a consists of chromatographically pure crystals and has a sharp melting point. Structure elucidation of the new phosphorus ylide 4a is based on the following evidence: elemental analyses and molecular weight determination (MS) of 4a support the molecular formula C 44 H 37 O 4 P (660.7); accordingly, MS: m/z ‫ס‬ 660 (M J CP ‫ס‬ 14.6 Hz, CHa) and at 125.98 (d, 1 J CP ‫ס‬ 105 Hz, P ‫ס‬ C) [11]. The reaction product of 1a with carbomethoxymethylenetriphenylphosphorane 2b and tert-butoxycarbonylmethylenetriphenylphosphorane 2c was assigned analogous structures 4b and 4c on the basis of comparable spectroscopic arguments (c.f.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compound 4a consists of chromatographically pure crystals and has a sharp melting point. Structure elucidation of the new phosphorus ylide 4a is based on the following evidence: elemental analyses and molecular weight determination (MS) of 4a support the molecular formula C 44 H 37 O 4 P (660.7); accordingly, MS: m/z ‫ס‬ 660 (M J CP ‫ס‬ 14.6 Hz, CHa) and at 125.98 (d, 1 J CP ‫ס‬ 105 Hz, P ‫ס‬ C) [11]. The reaction product of 1a with carbomethoxymethylenetriphenylphosphorane 2b and tert-butoxycarbonylmethylenetriphenylphosphorane 2c was assigned analogous structures 4b and 4c on the basis of comparable spectroscopic arguments (c.f.…”
Section: Resultsmentioning
confidence: 99%
“…Although the action of phosphonium ylides and trialkyl phosphites on diphenyl-1,2,3-propanetrione is well established [1,2], their action on 2-substituted-1,3-diphenylpropanetrione (1) has hitherto not been investigated. This, together with our interest in organophosphorus chemistry [3][4][5][6][7][8], has stimulated us to investigate the behavior of 1,3-diphenyl-2-(phenylmethylene)-1,3-propanedione (1a) and 1,3-diphenyl-2-(phenylimino)-1,3-propanedione (1b) toward a number of Wittig reagents of types 2a-e. A comparative study of the behavior of 1a,b toward trialkyl phosphites 3a-c is also reported (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of phosphorus ylides is an important reaction in organic chemistry because of the application of these compounds in the synthesis of organic products 1–29. Several methods have been developed for the preparation of phosphorus ylides 10,11.…”
Section: Introductionmentioning
confidence: 99%
“…Michael addition of phosphorus(III) compounds such as triphenylphosphine to acetylenic esters leads to reactive 1,3‐dipolar intermediate betaines, which are not detected even at low temperatures 14. These unstable species can be trapped by a protic reagent, ZH, such as methanol, amide, or imide, to produce various compounds, for example, ylides 4–29.…”
Section: Introductionmentioning
confidence: 99%